Breastfeeding and Its Associated Risk in Children with Acute Leukemia: A Retrospective Study - Lingappa, Appaji L; Kalapalar, Suresh R; Rudrappa, Sudha R; Manjunatha, SN (Indian Journal of Medical and Paediatric Oncology, 2018)
Aim: This study aims to study the protective risk association between the breastfeeding pattern and acute leukemia in children. Materials and Methods: Retrospective study in Kidwai Institute of Oncology, Bangalore. One hundred and twenty cases and 120 controls were enrolled during April 1, 2015–July 31, 2015. Cases include children diagnosed with acute leukemia either ALL or AML, between the age group of 1–15 years, with an elderly sibling and availability of biologic mother for collecting data regarding breastfeeding pattern. Controls include the elder sibling of the cases, children on compassionate care toward end of life, and also whose mother denied to give consent were excluded from the study. Statistical Analysis Used: Pearson Chi-square test, conditional logistic regression models, and Fischer's extract tests were used to assess the association between breastfeeding patterns and risk of acute leukemia. Results:: The acute leukemia cases and controls were similar with respect to sex, birthweight, maternal education, and socioeconomic status. Frequency of ever breastfeeding was same 99% in both cases and controls, odds ratio of ever breastfed to never breastfed (odds ratio = 1;95% confidence interval = 0.13–7.21) was not associated with risk of acute leukemia. Exclusive breastfeeding ≤2, 2–4 and 4–6 months as compared to exclusive breastfeeding beyond 6 months were associated with significant risk of acute leukemia and the P value trend is 0.0026. Similarly, continued breastfeeding till 1 year of age as compared to beyond 1 year was also associated with highly significant risk of acute leukemia with P value trend of 0.0001. Whereas continued breastfeeding till 2 years as compared to beyond 2 years was not associated with any risk of acute leukemia with P value trend of 0.3433. Conclusion: Significant association between breastfeeding and risk of acute leukemia was observed.
Keywords: Acute leukemia; breastfeeding; children